Psychometric longitudinal evaluation of the Chronic Acquired Polyneuropathy Patient‐Reported Index (CAPPRI) in patients with chronic inflammatory demyelinating polyneuropathy. Issue 1 (21st October 2020) - Sadjadi, Reza; Peric, Stojan; Gwathmey, Kelly; Bozovic, Ivo; Aleksa, Palibrk; Bjelica, Bogdan; Burns, Ted; Basta, Ivana
Abstract: Background: We studied the performance of a 15‐item, health‐related quality‐of‐life polyneuropathy scale in a longitudinal study of patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: Sixty‐one patients with CIDP completed the Chronic Acquired Polyneuropathy Patient‐Reported Index (CAPPRI) scale and Patient Impression of Change (PIC) at baseline and follow‐up visits. Clinicians completed Inflammatory Neuropathy Cause and Treatment (INCAT) disability scores at baseline and follow‐up visits. Conventional and modern psychometric analyses were performed on the completed forms. Results: CAPPRI was psychometrically stable between visits without significant difference in response pattern between visits 1 and 2 (paired t‐test P = .72). There was strong correlation between changes in INCAT and changes in CAPPRI scores between two visits (rho = 0.6, P < .001). In addition, we showed robust CAPPRI effect sizes between PIC categories. Conclusions: We demonstrated psychometric stability and construct longitudinal validity of CAPPRI.